Cryptic diversity across the Trans-Mexican Volcanic Belt of Mexico in the montane bunchgrass lizard Sceloporus subniger (Squamata: Phrynosomatidae) - Bryson, Jr., Robert W.; Grummer, Jared A.; Connors, Elizabeth M.; Tirpak, Joseph; Mccormack, John E.; Klicka, John (Zootaxa, 2021)
Sceloporus subniger Poglaygen & Smith is a montane bunchgrass lizard distributed across pine-oak forests of central Mexico. Prompted by the discovery of a new population of this lizard in far western Mexico, and by recent studies suggesting S. subniger may be a composite of several distinct species, we examined in more detail the genetic structure of S. subniger. We generated a mitochondrial DNA (mtDNA) dataset from 81 specimens and an ultraconserved elements (UCE) dataset representing thousands of genomic regions from 12 specimens to specifically evaluate the genetic distinctiveness of populations from western Michoacán and adjacent Jalisco along with the newly discovered population in the Sierra de Mascota in western Jalisco. We also recorded morphological data from 47 museum specimens to compare to our genetic data. Results from our analyses of the genetic data, augmented by specimen measurements and scale counts, support the notion that S. subniger is indeed a composite of distinct species. Montane bunchgrass lizards from western Michoacán and adjacent Jalisco, and from the Sierra de Mascota in western Jalisco, each represent distinct new species, which we describe and name here.